Changes in referral, treatment and outcomes in patients with systemic lupus erythematosus in Germany in the 1990s and the 2000s. Issue 1 (12th December 2014) - Albrecht, Katinka; Huscher, Dörte; Richter, Jutta; Backhaus, Marina; Bischoff, Sascha; Kötter, Ina; Thiele, Katja; Zink, Angela
Abstract : Objective: To evaluate trends in the referral, treatment and outcome of patients with systemic lupus erythematosus (SLE) in Germany over two decades. Methods: From 1993 to 2012, ∼1200 patients with SLE were recorded annually in the national database of the German Collaborative Arthritis Centres. Treatment patterns, healthcare use and outcomes, such as disease activity, function and work participation, were evaluated over time. Furthermore, two distinct cohorts of patients (enrolment 1994–1998, n=467; and 2004–2008, n=376) observed over 5 years were assessed for changes in outcomes. Results: The mean disease duration at the first visit to a rheumatologist decreased from 2.6 (1994) to 1.5 (2012) years. Glucocorticoids (69%), antimalarials (56%), azathioprine (22%), non-steroidal anti-inflammatory drugs (23%) and mycophenolate mofetil (15%) were the most frequently used treatments in 2012. A significant increase was observed in the use of antimalarials and mycophenolate mofetil. The use of glucocorticoids at >7.5 mg/day decreased from 27% (1994) to 10% (2012). The average length of sick leave taken due to SLE declined from 9 weeks (1997) to 6 weeks (2012). When comparing the two longitudinal cohorts, in the cohort from the 2000s, the intraindividual decline of disease activity was significantly stronger (p<0.001), and fewer patients retired early (36% vs 46%). Conclusions: The disease activity and resource use declined considerably over the observation period, and more patients remained in the labour force. Earlier treatment onset, faster modification of the treatment regimen and more intensive use of anti-inflammatory therapy may account for the improved outcomes in patients with SLE across the years.